pengaruh pelatiha, lingkungan kerja dan kepuasan kerja terhadap komitmen organisasi karyawan galeri smartfren timoho kota yogyakarta - Hendrikus Ricky Lauranda (JURNAL EKOBIS DEWANTARA, 2018)
The purpose of this study was to analyze the influence training on organizational commitment, influence work environment on organizational commitment, influence work satisfaction onorganizational commitment , and influence training, work environment and work satisfaction onorganizational commitment Gallery Smartfren Timoho Yogyakarta City. The population of this study is all employees at Gallery Smartfren Timoho Yogyakarta City. The sampels is about 45 employees. Data collection using a questionnaire, while data analysis techniques using multiple regression analysis by the F-test and T-test, and the classical assumption test of multicollinearity test, normality test, and heteroscedasticity. The results influence training have significant effect on Organizational Commitment, work environment have significant effect on Organizational Commitment, work satisfaction have significant effect on Organizational Commitment, and training, work environment, and work satisfaction has significant effect on organizational commitment employees at Gallery Smartfren Timoho Yogyakarta City. The results with level of significant 5% or 0,05 showed labor training haven significant effect on organizational commitment (0,016 < 0,05), work environment have significant effect on organizational commitment (0,012 < 0,05), work satisfaction have significant effect on organizational commitment (0,015 < 0,05) and labor training, work environment and work satisfaction has significant effect on organizational commitmen Gallery Smartfren Timoho Yogyakarta City.